A place in the sun : Africa in Italian colonial culture from post-unification to the present - Palumbo, Patrizia (University of California Press, 2003)
Given the centrality of Africa to Italy's national identity, a thorough study of Italian colonial history and culture has been long overdue. Two important developments, the growth of postcolonial studies and the controversy surrounding immigration from Africa to the Italian peninsula, have made it clear that the discussion of Italy's colonial past is essential to any understanding of the history and construction of the nation.